Analisis Prinsip Kerja Sama pada Podcast Gaspol Kanal kompas.com Edisi Pilgub Banten dan Potensinya sebagai Bahan Ajar di SMA - Sulistiana, Ilma; Saraswati, Saraswati; Meliyawati, Meliyawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study analyzes the compliance with and violations of Grice’s cooperative principle in the Gaspol Kompas.com podcast episode on the Banten gubernatorial election and examines the potential use of these findings as instructional material for teaching debate in senior high schools. The study employs spontaneous political conversation as its data, which distinguishes it from previous research that commonly used scripted sources such as novels, dramas, films or nonpolitical podcasts. A descriptive qualitative method was applied, using observation and note taking techniques. The findings reveal various forms of compliance with and violations of the maxims of quantity, quality, relatin and manner within political discourse. These findings hold potential as argumentative examples in debate learning, although the study does not develop or test any instructional materials directly. The novelty of this research lies in its analysis of spontaneous political conversations and their relevance to Indonesian language learning, an aspect that has not been highlighted in previous studies.